2017
DOI: 10.1080/10428194.2017.1361025
|View full text |Cite
|
Sign up to set email alerts
|

KITmutations correlate with adverse survival in children with core-binding factor acute myeloid leukemia

Abstract: The prevalence and clinical relevance of KIT mutations in childhood core-binding factor (CBF) acute myeloid leukemia (AML) have not been well characterized. In this study, a total of 212 children with de novo AML were enrolled from a Chinese population and 50 (23.5%) of the patients were deemed CBF-AML. KIT mutations were identified in 30% of the CBF-AML cohort. The KIT mutations were clustered in exon 17 and exon 8, and KIT mutations in exons 8 and 17 were correlated with a shorter overall survival (OS) (5-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 46 publications
7
17
1
Order By: Relevance
“…Unlike the study by Klein and colleagues and our previous study cohort, the uniform conventional chemotherapy backbone used in this study cohort may have facilitated our ability to detect differences in outcome for KIT þ disease. Similar to the 4 other pediatric studies in which prognostic significance was noted (17,22,27,45), our study Association of E17 mutations with outcomes in CBF AML. A, DFS in CBF patients for KIT E17 þ compared with KIT À patients.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Unlike the study by Klein and colleagues and our previous study cohort, the uniform conventional chemotherapy backbone used in this study cohort may have facilitated our ability to detect differences in outcome for KIT þ disease. Similar to the 4 other pediatric studies in which prognostic significance was noted (17,22,27,45), our study Association of E17 mutations with outcomes in CBF AML. A, DFS in CBF patients for KIT E17 þ compared with KIT À patients.…”
Section: Discussionsupporting
confidence: 85%
“…A second recent meta-analysis by Chen and colleagues found that outcomes were inferior in KIT þ CBF AML overall, and specifically in KIT þ t(8;21) (15). Four additional pediatric studies found that KIT mutations adversely affected OS, DFS, and RR in pediatric t(8;21) AML (17,22,27,45). Conversely, a more recent series of t(8;21) pediatric patients with CBF AML enrolled on multiple cooperative group clinical trials failed to demonstrate prognostic significance of KIT þ disease (2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with our observation that KIT promotes erythroid at the expense of myeloid cell fate, gain-of-function mutations in the Kit coding sequence have been described to trigger clonal expansion of malignant pro-erythroblasts in murine erythroleukemia (Kosmider et al, 2005). Moreover, gain-of-function mutations have been associated with human adult and pediatric core binding factor acute myeloid leukemia (CBF-AML), for which KIT mutations are poor prognostic factors (Cairoli et al, 2006;Chen et al, 2018;Krauth et al, 2014). It should therefore be investigated whether KIT mutations also contribute to human erythroleukemia.…”
Section: Discussionsupporting
confidence: 87%
“…KIT D816V mutations were reported in 4%‐28% and strongly associated with poorer DFS (6%‐48%) . In pediatric populations, KIT mutations clustered in exon 17 and exon 8 were identified in 20‐30% of the CBF‐AML patients, yet its effect on prognosis is not agreed upon . A meta‐analysis indicated KIT mutation increased relapse risk (RR at 2 years 1.76 [95% CI: 1.45‐2.12]) and decreased OS 1.35 (95% CI: 1.09‐1.66) …”
Section: Discussionmentioning
confidence: 99%